2022
DOI: 10.3390/ma15062238
|View full text |Cite
|
Sign up to set email alerts
|

Powder Reuse in Laser-Based Powder Bed Fusion of Ti6Al4V—Changes in Mechanical Properties during a Powder Top-Up Regime

Abstract: The properties of Extra Low Interstitials (ELI) Ti6Al4V components fabricated via the laser-based powder bed fusion (L-PBF) process are prone to variation, particularly throughout a powder reuse regime. Interstitial pick-up of interstitial elements within the build chamber during processing can occur, most notably, oxygen, nitrogen, and hydrogen, which can impair the mechanical properties of the built component. This study analyses ELI Ti6Al4V components manufactured by the L-PBF process when subjected to a ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…These changes in the powder material were found to translate into changes in the resulting part properties, such as an increase in the surface roughness and increased porosity. These conclusions agreed with other studies across a range of different metal powders commonly used in the L-PBF process [4][5][6][7][8]. The resulting part quality from the L-PBF process is highly dependent on several factors, including the laser parameters, CAD geometries, and processing conditions, for example [9].…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…These changes in the powder material were found to translate into changes in the resulting part properties, such as an increase in the surface roughness and increased porosity. These conclusions agreed with other studies across a range of different metal powders commonly used in the L-PBF process [4][5][6][7][8]. The resulting part quality from the L-PBF process is highly dependent on several factors, including the laser parameters, CAD geometries, and processing conditions, for example [9].…”
Section: Introductionsupporting
confidence: 88%
“…As a result of the changes in the powder particle size and shape during powder The resulting part quality from the L-PBF process is highly dependent on several factors, including the laser parameters, CAD geometries, and processing conditions, for example [9]. It is well understood that the characteristics of the raw input material, in this case a metal powder, affect the resulting qualities of the parts produced [1,3], research in previous years has reported the interdependent nature of the powder properties and resulting output parts manufactured [6,7]. Figure 2 The resulting part quality from the L-PBF process is highly dependent on several factors, including the laser parameters, CAD geometries, and processing conditions, for example [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations